Cover picture: Synthesis of binary metal–metal oxide core‐shell nanoparticles via surfactant‐free intercation redox reactions (BKCS 08/2022). (16th August 2022) - Yim, Gyeonghye; Cho, Sanghyuk; Park, Jung Tae; Jang, Hongje
Abstract: One‐pot synthesis of bimetallic core‐shell nanostars without toxic surfactant, morphology‐controlling molecules, and reducing agents was implemented here only with metal cations. The spontaneous inter‐cation redox reaction between the pair of early transition metal elements and noble metal elements formed photocatalytic metal‐metal oxide core‐shell nanoparticles. Abstract : One‐pot synthesis of bimetallic core‐shell nanostars without toxic surfactant, morphology‐controlling molecules, and reducing agents was implemented here only with metal cations. The spontaneous inter‐cation redox reaction between the pair of early transition metal elements and noble metal elements formed photocatalytic metal‐metal oxide core‐shell nanoparticles.